Solid‐State Crosslinkable, Shape‐Memory Polyesters Serving Tissue Engineering. Issue 8 (17th February 2023) - Delaey, Jasper; Parmentier, Laurens; Pyl, Lincy; Brancart, Joost; Adriaensens, Peter; Dobos, Agnes; Dubruel, Peter; Van Vlierberghe, Sandra
Abstract: Acrylate‐endcapped urethane‐based precursors constituting a poly(D, L‐lactide)/poly( ε ‐caprolactone) (PDLLA/PCL) random copolymer backbone are synthesized with linear and star‐shaped architectures and various molar masses. It is shown that the glass transition and thus the actuation temperature could be tuned by varying the monomer content (0–8 wt% ε ‐caprolactone, T g, crosslinked = 10—42 °C) in the polymers. The resulting polymers are analyzed for their physico‐chemical properties and viscoelastic behavior (G′max = 9.6–750 kPa). The obtained polymers are subsequently crosslinked and their shape‐memory properties are found to be excellent ( R r = 88–100%, R f = 78–99.5%). Moreover, their potential toward processing via various additive manufacturing techniques (digital light processing, two‐photon polymerization and direct powder extrusion) is evidenced with retention of their shape‐memory effect. Additionally, all polymers are found to be biocompatible in direct contact in vitro cell assays using primary human foreskin fibroblasts (HFFs) through MTS assay (up to ≈100% metabolic activity relative to TCP) and live/dead staining (>70% viability). Abstract : In this articl, the synthesis and characterization of novel shape‐memory polymers are discussed. The polymers constitute amorphous linear and star‐shaped PDLLA/PCL backbones. The backbones are joined to an acrylate PEG spacer using a diisocyanate to obtain solid‐state crosslinkable materials. The developed materials are characterized for their shape‐memory properties, crosslinking properties, thermal properties, degradation, and processing using various additive manufacturing techniques.